PENCIPTAAN ILUSTRASI PERMAINAN TRADISIONAL SEBAGAI PENINGKATAN KETERAMPILAN MOTORIK ANAK USIA DINI - Ruhul Amin (Universitas Sarjanawiyata Tamansiswa, 2022)
Traditional games are one of the traditions that are starting to be forgotten byyoung generations. This is because the advance of technology that is more enjoyable orfun. However, this will have a negative impact, especially on children's motor development. Therefore, through the creation of this illustration paintings, the author wants to reintroduce the traditional games and try to improve the motor skills of children through these works. The method of creation carried out by the author is through exploration from various aspects, such as ideas, concepts, media, and techniques. The author also performs asimulation in the form of sketching to facilitate the creation of the work. The results of thisexploration and simulation are then visualized into illustration paintings using acrylic colorson canvas. The work was made with a total of 10 paintings. The games used as source ofthe works include: Ular Naga, Cublak-Cublak Suweng, Lompat Tali, Congklak, Engklek,Benthik, Boy-Boyan, Jejamuran, Obar-Abir, Dhingklik Oglak Aglik.